2015
DOI: 10.1073/pnas.1503395112
|View full text |Cite
|
Sign up to set email alerts
|

CB2 cannabinoid receptor agonist enantiomers HU-433 and HU-308: An inverse relationship between binding affinity and biological potency

Abstract: Activation of the CB2 receptor is apparently an endogenous protective mechanism. Thus, it restrains inflammation and protects the skeleton against age-related bone loss. However, the endogenous cannabinoids, as well as Δ(9)-tetrahydrocannabinol, the main plant psychoactive constituent, activate both cannabinoid receptors, CB1 and CB2. HU-308 was among the first synthetic, selective CB2 agonists. HU-308 is antiosteoporotic and antiinflammatory. Here we show that the HU-308 enantiomer, designated HU-433, is 3-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 49 publications
9
47
0
2
Order By: Relevance
“…(K i hCB 2 R < 13 nm)w ith at least 86-fold selectivity over hCB 1 R. In line with Mechoulam's report, [31] compounds ent-1, ent-10-Cl and ent-11 showedl ower hCB 2 Ra ffinity than their enantiomers by af actor of ca. 10 (hCB 2 R K i < 121 nm)b ut retained high selectivity over hCB 1 R( hCB 1 R K i > 3.1 mm).…”
Section: In Vitro Pharmacological Characterizationsupporting
confidence: 83%
See 1 more Smart Citation
“…(K i hCB 2 R < 13 nm)w ith at least 86-fold selectivity over hCB 1 R. In line with Mechoulam's report, [31] compounds ent-1, ent-10-Cl and ent-11 showedl ower hCB 2 Ra ffinity than their enantiomers by af actor of ca. 10 (hCB 2 R K i < 121 nm)b ut retained high selectivity over hCB 1 R( hCB 1 R K i > 3.1 mm).…”
Section: In Vitro Pharmacological Characterizationsupporting
confidence: 83%
“…expectation based on radioligand binding studies, which attested HU-308'sh igher CB 2 Ra ffinity when compared to HU-433. [31] Therefore, ent-1 was included in the presents tudy in order to maximize the chance of identifying irreversible and selective CB 2 Rl igands. Compound ent-1 was accessed by Friedel-Crafts alkylation with ent-8 derived from (1R)-(À)-myrtenol and subsequent elaboration analogous to the sequence shown in Scheme 2( see SupportingI nformation).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the pinene dimethoxy-dimethylheptyl-CBD derivative HU-308 [(3R, 4S, 6S)-2-[2,6-dimethoxy-4-(2-methyloctan-2-yl)phenyl]-7,7-dimethyl-4-bicyclo[3.1.1]hept-3-enyl]methanol] and its enantiomer HU-433 [(3S, 4R, 6R)-2-[2,6-dimethoxy-4-(2-methyloctan-2-yl)phenyl]-7,7-dimethyl-4bicyclo[3.1.1]hept-3-enyl]methanol] were shown to have specific agonistic activity for the CB2 receptor (Table 2), and consequently, anti-inflammatory activity in cultured calvarial osteoblasts from C57BL/6J mice [125]. However, it has been found that HU-433 exhibits greater anti-inflammatory activity with poorer CB2 receptor binding affinity ( Table 2) [125]. In contrast, HU-308, a CB2 agonist, was found to decrease TNF-α-induced expression of ICAM-1 and VCAM-1 in sinusoidal endothelial cells of human liver tissue [24].…”
Section: Cb1/cb2 Receptorsmentioning
confidence: 99%
“…Table 2. Influence of natural and synthetic CBD derivatives on receptor activation (X: agonist activation or Y: antagonist activation by related CBD derivative; * weak affinity; #: full name is in chapter 4.1) [2,24,72,76,[114][115][116]120,[122][123][124][125][126][127]130]. Natural CB1 CB2 Gpr55 Gpr18 TRPV1 TRPA1 TRPM8 5-HT…”
Section: Trpv1 5-ht 1a and Adenosine A 2a Receptorsmentioning
confidence: 99%
“…Preclinical studies show that synthetic CB2 agonists rescue ovariectomy-induced bone loss, suggesting that these drugs may improve osteoporosis (805). In women, 17␤-estradiol administration inhibits activity and formation of osteoclasts in vitro and increases CB2 expression, which may underlie the antiresorptive properties of estrogen and postmenopausal osteoporosis (745).…”
Section: Bonementioning
confidence: 99%